1968
DOI: 10.1901/jaba.1968.1-99
|View full text |Cite
|
Sign up to set email alerts
|

BEHAVIORAL ENGINEERING: POSTURAL CONTROL BY A PORTABLE OPERANT APPARATUS1

Abstract: Recent studies suggested a general behavioral engineering approach to behavioral disorders by portable operant treatment instruments. The approach was applied to the problem of poor posture, specifically rounding of the back or slouching. An apparatus was developed that provided a warning stimulus followed by an aversive tone for the duration of slouching. Slouching was thereby punished by onset of the tone, and non-slouching was reinforced by tone termination and postponement. Twenty-five adults wore the appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Doane (1959), in a correlational study, reported a positive relationship between academic performance and the sitting posture of high school students. Azrin, Rubin, O'Brien, Ayllon, and Roll (1968), noting that proper posture is a matter of aesthetic as well as medical concern, have suggested that if the posture of mentally retarded and mentally ill residents in institutions were improved, it might facilitate successful discharge and greater acceptance of them by the community at large.…”
Section: Discussionmentioning
confidence: 99%
“…Doane (1959), in a correlational study, reported a positive relationship between academic performance and the sitting posture of high school students. Azrin, Rubin, O'Brien, Ayllon, and Roll (1968), noting that proper posture is a matter of aesthetic as well as medical concern, have suggested that if the posture of mentally retarded and mentally ill residents in institutions were improved, it might facilitate successful discharge and greater acceptance of them by the community at large.…”
Section: Discussionmentioning
confidence: 99%
“…Gross motor behavior of a simplified nature has also been developed in normal adults. In two studies using portable operant apparatus, the posture of adults was improved from a slouching position to a proper postural position (Azrin, Rubin, O'Brien, Ayllon, & Roll, 1968;O'Brien & Azrin, 1970). Further progress in utilizing operant procedures for developing gross motor skills in a normal population was made by Hardiman, Goetz, Reuter, and LeBlanc (1975) with a preschool child (walking longitudinally through a ladder, climbing stairs, sliding down a board, rolling on the ground, climbing a ladder, and walking on a balance board).…”
mentioning
confidence: 99%
“…Meyer and Mair (1963) described a portable apparatus for achieving this same objective, and reported that it was useful for the clinical treatment of stuttering but, unfortunately, provided no quantitative data as to its effectiveness. The rationale for developing the apparatus here stemmed from the behavioral engineering approach described elsewhere (Azrin, Rubin, O'Brien, Ayllon, and Roll, 1968;Azrin and Powell, 1968). The target behavior was defined as rhythmic speech and the specific response was defined as the spoken word.…”
Section: Discussionmentioning
confidence: 99%